Jak konceptualizujemy riposty? Raport z badań - Laskowski, Wojciech (Investigationes Linguisticae, 2008)
In order to investigate the conceptualization of retort, the author administered a questionnaire to 86 students. Its results showed that there was a high level of agreement among the respondents in the way they understood and defined retorts. Retorts were related to the war domain and interpersonal attacks. The results are discussed with respect to the relational models of communication, especially to the model of interactional confirmation and disconfirmation by K.N.L. Cissna & E. Sieburg.